2018
DOI: 10.1002/ajpa.23434
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal behavior by a diurnal ape, the West African chimpanzee (Pan troglodytes verus), in a savanna environment at Fongoli, Senegal

Abstract: Animals in highly seasonal habitats often exhibit thermoregulatory adaptations but, like other primates, chimpanzees lack physiological mechanisms to combat thermal stress. This study provides evidence that they may exhibit behaviors that allow them to avoid high temperatures in a savanna environment, such as feeding and socializing at night during the hottest time of year and in the brightest moon phases. The results support theories invoking thermal stress as a selective pressure for hominins in open environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 47 publications
(59 reference statements)
2
44
0
1
Order By: Relevance
“…There is little information for dispersal distances between chimpanzee communities, for example when females transfer from their natal group. Published maximum daily travel distances range from 9 km in rainforest habitat (Herbinger et al 2001) to 16 km in drier habitat (Humle et al 2011), and may be larger in very dry areas where chimpanzees have larger home ranges (Pruetz 2018). However, this is likely only the case within suitable habitat and in the absence of barriers such as areas densely populated by humans.…”
Section: Identifying Populations and Low-connectivity Areasmentioning
confidence: 99%
“…There is little information for dispersal distances between chimpanzee communities, for example when females transfer from their natal group. Published maximum daily travel distances range from 9 km in rainforest habitat (Herbinger et al 2001) to 16 km in drier habitat (Humle et al 2011), and may be larger in very dry areas where chimpanzees have larger home ranges (Pruetz 2018). However, this is likely only the case within suitable habitat and in the absence of barriers such as areas densely populated by humans.…”
Section: Identifying Populations and Low-connectivity Areasmentioning
confidence: 99%
“…Finally, by definition, fission–fusion animals are dispersed at various times during the day and night, and thus calls may serve coordination and cohesive mechanisms (Leighty, Soltis, Wesolek, & Savage, ), advertising a caller's location and facilitating reunions (e.g., fusion events) later the next day. Environmentally, primates that live in hot climates may forage at night to avoid high day‐time temperatures (Pruetz, ). By being active during periods of the night, animals can increase their foraging time and ultimately, increase their caloric intake.…”
Section: Introductionmentioning
confidence: 99%
“…At Seringbara, Koops et al () found chimpanzee nest height increased with increasing humidity. Temperature during the day can also affect great ape sleeping patterns at night, as shown in Fongoli by Pruetz (), whereby increased nocturnal activity appeared to be the result of compensating for thermal stress experienced during the day. Evidence provided in this issue suggests that chimpanzees adjust nest shape and architecture in response to local weather conditions (Stewart, Piel, Azkarate, & Pruetz, ).…”
Section: Great Ape Nesting Behavior and Proximate Functions Of Greatmentioning
confidence: 99%
“…Temperature is another environmental factor that has been shown to influence pattern and quality of sleep in lemurs (Samson, Bray, & Nunn, ). and chimpanzees (Pruetz, ). While the external drivers mentioned above may trigger nocturnal activity in diurnal great apes, internal factors, such as the need to defecate (K. Zamma, pers.…”
Section: Historical Aspects Of Sleep Researchmentioning
confidence: 99%
See 1 more Smart Citation